THE INFLUENCE OF MACROECONOMIC VARIABLES TO STOCK MARKET RETURNS OF THREE SECTORS (AGRICULTURE, PROPERTY, AND MINING) IN INDONESIA - Muslimin, Ihwanul (Jurnal Ilmiah Mahasiswa FEB, 2021)
The objective of this research was to determine the effect of macroeconomic variables such as inflation (CPI), exchange rate (ER), money supply (M2) and additional dummy variables to distinguish stock prices of 5000 and stock prices above 5000 on stock returns in three sectors such as agriculture, mining and property on the Indonesia Stock Exchange and the data used is panel data consisting of monthly data from 2008 to 2018. Based on the research, it was found that there was no significant effect between inflation (CPI) and stock market returns and also The exchange rate variable (ER) has no significant effect on stock market returns. Furthermore, The money supply (M2) variable has a significant influence on stock market returns. An increased in money supply (M2) has an impact on increasing stock returns and simultaneously inflation (CPI), Exchange rate (ER) and money supply (M2) have a significant influence on stock market returns in the three sectors of agriculture, mining and property.Keyword:Macroeconomic Variable, Stock Market Returns, Indonesia,Panel analysis